Determinan Penyerapan Tenaga Kerja Sektor Pertanian di Provinsi Jawa Tengah dengan Pendekatan Data Panel Periode 2010-2021 - Yoga Adi Pratama; Nur Hidayah (Ekonomis: Journal of Economics and Business, 2023)
Labor has an important role in economic development, especially in the agricultural sector, but it will be a problem if the amount of Labor is not proportional to the available employment. This is a challenge for the government to be able to provide employment along with the increasing labor force. This study aims to determine the effect of Gross Regional Domestic Product, Human Development Index, Minimum wage, open unemployment on employment in the agricultural sector in Central Java province. The results of panel data regression concluded that the model selected in the panel data is FEM with the results of the open unemployment rate variable has a positive and significant effect on agricultural sector labor, but the minimum wage, HDI, GDP variables have a positive and insignificant effect on Labor. Validity test of influence in the FEM model concluded in the F test variable minimum wage, HDI, GDP, TPT together influence on Labor. R-square in the FEM model of 77.44% of the variables in the model affect the workforce. Based on the results of the estimates, the effect of GDP, HDI, Minimum wage, open unemployment rate is positive. The open unemployment rate variable has an effect on HDI, but the GDP variable, Human Development Index and minimum wage have no effect on the agricultural sector workforce. GDP variable does not affect the agricultural sector labor with a probability of 0.3196. Human development index variable has no effect on the agricultural sector workforce of 0.1509. The district minimum wage variable has no effect on the agricultural sector workforce of 0.8503. Variable open unemployment rate affects the agricultural sector workforce of 0.0000. F test of 0.0000 means that the variables GDP, HDI, Minimum wage, open unemployment rate jointly affect the agricultural sector workforce.